Integrasi Sistem MRP ke Sistem ERP Oracle pada PT Ultrajaya Milk Industry di Bandung Barat - Megananda, Sangjaya; Mogensyah, Torang; Ramadhanty, Nadyfa; Rudiyono, Heimemayu (PENG: Jurnal Ekonomi dan Manajemen, 2025)
This article discusses the integration of the Material Requirement Planning (MRP) system into the Enterprise Resource Planning (ERP) system at PT Ultrajaya Milk Industry in West Bandung. In the context of increasingly fierce industrial competition and the economic challenges faced, it is important for companies to optimize production and inventory management systems. This research aims to identify the urgency of developing an MRP system into an Enterprise Resource Planning (ERP) system and analyze how this integration system can help PT Ultrajaya overcome existing challenges. The methods used in this research include literature study and analysis of relevant secondary data. The research results show that the development of the MRP system to ERP not only increases operational efficiency but also improves product quality and availability of goods on the market. It is hoped that this article will provide insight for industrial practitioners and academics regarding the importance of an integrated management system in increasing a company's competitiveness.